Structural, dielectric and magnetic properties of Bi–Mn doped SmFeO3. Issue 7 (May 2020) - Nancy,; Shukla, Rishabh; Dhaka, Raveena; Dash, Shubhra; Sahoo, Subasa Chandra; Bahera, Banarji; Babu, P.D.; Choudhary, Ramjanay; Patra, Ajit Kumar
Abstract: We have studied the structural, magnetic, dielectric and impedance properties of the Sm1-x Bix Fe1-y Mny O3 [SmFeO3 (SFO), Sm0.9 Bi0.1 FeO3 (SBFO), Sm0.9 Bi0.1 Fe0.9 Mn0.1 O3 (SBFMO)] polycrystalline samples synthesized by solid-state reaction method. Rietveld refinement of room temperature (RT) powder x-ray diffraction pattern confirms the orthorhombic crystal structure with Pnma/Pbnm space group. The average particle size of Bi doped and co-doped (Bi–Mn) samples determined from SEM analysis are 5.6 μm and 5.2 μm, respectively. Room temperature field-dependent magnetization increases, suggesting the presence of magnetic contribution due to the Rare earth-Fe ion interaction which persists even at RT. However, with co-doping of Bi and Mn, a decrease in magnetization is observed, which corresponds to the dilution of Fe 3+ -Fe 3+ interactions due to the presence of Mn 3+ ions. The observed values of magnetization at 90 kOe for Bi doped sample is (2.87 emu/g) approximately two times and for codoped (0.7 emu/g) sample is nearly half of that of pristine sample (1.51 emu/g). Dielectric measurements as a function of frequency/temperature and impedance analysis using equivalent circuit model reveal grain and grain boundary contributions of SBFO (at high temperature) and SBFMO (for all temperature) samples towards the electrical properties indicating the electrically heterogeneous nature of these samples. However, for SFO sample grain contribution is dominant. Observed value of dielectric constant varies from 10 3 -10 4 with Bi–Mn doping. The conduction mechanism of the studied samples has been explained by considering Jonscher power law. Arrhenius law fitting of AC conductivity data manifests two types of conduction mechanisms in these samples. The depressing nature of the semicircular arc observed in the Nyquist plot of all the samples indicates the presence of a non-Debye type of relaxation.